2013
DOI: 10.1038/ncb2864
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of robustness in spindle assembly checkpoint signalling

Abstract: The spindle assembly checkpoint is a conserved signalling pathway that protects genome integrity. Given its central importance, this checkpoint should withstand stochastic fluctuations and environmental perturbations, but the extent of and mechanisms underlying its robustness remain unknown. We probed spindle assembly checkpoint signalling by modulating checkpoint protein abundance and nutrient conditions in fission yeast. For core checkpoint proteins, a mere 20% reduction can suffice to impair signalling, rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
124
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(136 citation statements)
references
References 82 publications
10
124
2
Order By: Relevance
“…Thus, miR-28-5p-mediated regulation of Mad2 may normally be dedicated to fine-tune Mad2 levels to balance against stressinduced numerical chromosomal instability. This interpretation is in line with recent findings that amounts of checkpoint proteins dictate the strength of the mitotic checkpoint (35)(36)(37). Accordingly, miR-28-5p may be part of a mechanisms that provides robustness to the process of mitosis assuring errorfree chromosome segregation.…”
Section: Discussionsupporting
confidence: 77%
“…Thus, miR-28-5p-mediated regulation of Mad2 may normally be dedicated to fine-tune Mad2 levels to balance against stressinduced numerical chromosomal instability. This interpretation is in line with recent findings that amounts of checkpoint proteins dictate the strength of the mitotic checkpoint (35)(36)(37). Accordingly, miR-28-5p may be part of a mechanisms that provides robustness to the process of mitosis assuring errorfree chromosome segregation.…”
Section: Discussionsupporting
confidence: 77%
“…The expression and/or localization of SAC proteins are finely modulated to regulate APC/C activity (Musacchio and Salmon, 2007) in a dose-dependent manner (Collin et al, 2013;Heinrich et al, 2013). The robustness of the SAC is, in part, determined by the amount of MAD2 recruited to kinetochores.…”
Section: Traip Depletion Decreases Mad2 Levels At Unattached Kinetochmentioning
confidence: 99%
“…4E,F). This might be physiologically relevant, because a reduction of 20% in MAD2 levels is sufficient to impair SAC activity in yeast (Heinrich et al, 2013).…”
Section: Traip Depletion Decreases Mad2 Levels At Unattached Kinetochmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that the length of mitotic arrest and presumably the strength of the spindle checkpoint can be tuned by the number of unattached kinetochores or the severity of spindle damage (41)(42)(43). We wondered whether the Phe and D boxes of BubR1 were required for the less robust mitotic arrest triggered by low concentrations of taxol (Fig.…”
Section: The Phe and D Boxes Of Bubr1 Are Dispensable For The Spindlementioning
confidence: 99%